Korelasi Penggunaan Media Pembelajaran Canva Terhadap Motivasi Belajar Peserta Didik - Mustakim, Abd.; Halik, Abdul; Akib, Muh.; Saleh, Muhammad; Kaharuddin, Kaharuddin; Ismail, Indriani H. (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – The objective of this study is to examine the correlation between the use of Canva-based SKI instructional videos and student motivation at MAS DDI As-Salman Allakuang. It aims to determine how Canva's integration influences aspects of student motivation such as interest, effort, and perseverance, providing insights into the effectiveness of digital learning tools in enhancing student engagement and motivation.Method – This study employs a quantitative correlational design to measure the impact of using Canva-based SKI instructional videos on student motivation at MAS DDI As-Salman Allakuang. A purposive sample of 54 students was selected. Data were collected using a validated motivation questionnaire covering aspects like interest, effort, and perseverance. Pearson correlation statistics were used to analyze the relationship between the use of Canva-based SKI instructional videos and student motivation.Findings – This study found a significant moderate positive correlation (r=0.617, p=0.001) between the use of Canva-based SKI instructional videos and student motivation in Aqidah Akhlak learning at MAS DDI As-Salman Allakuang. This indicates that more frequent use of Canva-based videos is associated with higher student motivation. These findings confirm the hypothesis and demonstrate that digital learning tools like Canva can enhance student motivation. Research Implications – Using Canva-based instructional videos in Aqidah Akhlak learning can practically enhance student motivation. However, to confirm this effect, more diverse, experimental, and long-term studies are needed due to limitations in causation and potential biases.